1995
DOI: 10.1007/bf01379399
|View full text |Cite
|
Sign up to set email alerts
|

Vagina dentata revisited: Gender and asymptomatic shedding of genital herpes

Abstract: Medical research on genital herpes indicates that women shed herpes asymptomatically. This paper examines the medical understanding of asymptomatic shedding of herpes among women as partial knowledge, meaning biased and incomplete, based upon folk models of male and female sexual bodies and upon the structure of medical practice. The focus on women's sexual anatomy as dangerous to men and the lack of a medical specialty on male reproductive/sexual health results in blaming women for transmission of sexual dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In contrast, the anatomy of the genital tract in men and the fact that the genital epithelium is predominantly skin and not mucosa have made less plausible the concept of asymptomatic shedding from men's genital skin. This issue was illustrated in a study of physicians' attitudes toward asymptomatic shedding of HSV, 31 in which both male and female physicians tended to dismiss the possibility of asymptomatic shedding in men as anatomically implausible. We found that this reasoning is erroneous; the rates of subclinical shedding among men approximated those among women.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the anatomy of the genital tract in men and the fact that the genital epithelium is predominantly skin and not mucosa have made less plausible the concept of asymptomatic shedding from men's genital skin. This issue was illustrated in a study of physicians' attitudes toward asymptomatic shedding of HSV, 31 in which both male and female physicians tended to dismiss the possibility of asymptomatic shedding in men as anatomically implausible. We found that this reasoning is erroneous; the rates of subclinical shedding among men approximated those among women.…”
Section: Discussionmentioning
confidence: 99%